A Retrospective Observational Analysis on the Outcome of Microlumbar Discectomy among 70 Consecutive Cases in the Tertiary Care Spine Center in Nepal - Bhattarai, Binod; Sah, Shashi Bhushan (Nepal Journal of Neuroscience, 2019)
Lumbar disc disease is a commonly encountered spine problem. There have been various modalities of treatment that have evolved over the years. The objective of our study is to analyze safety, efficacy, and complications following Micro-lumbar discectomy. All the cases admitted in our spine clinic with symptomatic lumbar disc and who underwent Micro-lumbar discectomy between February2013 to February 2018 were included in our study. Seventy cases were operated during this period. Total operative time, immediate and long term outcome with regards to pain and neurological deficits were tabulated and analyzed for each patient. Furthermore, short and long term complications including wound infection, discit is, instability and recurrence at the same level were also studied and compared with similar studies from the literature. None of our cases had complications related to wound infection, instability or post-operativediscitis. Immediate relief from the radicular pain experienced in the pre-operative period was seen in all patients (Visual analog scale) though benign tingling sensation persisted in a few of them that improved in a short span of time. Recurrence was seen in only one case. Micro-lumbar discectomy is a minimally invasive spine procedure conferring high benefits to the patients. While compared to other methods of intervention, it has a low risk of complications as well as chances of disc recurrences.